Os saberes das práticas corporais indígenas na educação física escolar - Barale, Thaisa Santos (2024)
Given the need to address indigenous body culture in school Physical Education classes, this research began with the question: What are the pedagogical potentials of developing an educational product for Physical Education teachers about indigenous body practices in collaboration with students from the Indigenous Licentiate program at UFG? The general objective was to design, develop, and analyze an educational product about indigenous body practices for Physical Education teachers working in intermediate years of Elementary Education who have little or no knowledge on the subject. The initial hypothesis of the research was that developing an educational product proposal about indigenous culture, built in partnership with students from the Intercultural Indigenous Licentiate course, promotes a school education focused on otherness, recognizing the right to difference. For this research, we used principles of educational action research, which sought to improve practices through reflection and collaborative action. Three groups participated in the research: the first composed of students from the Intercultural Indigenous Licentiate course, the second by elementary school students, and the third by Physical Education teachers. Data collection was carried out using questionnaires and semi-structured interviews, and data analysis was performed using Content Analysis techniques through a qualitative approach. For data collection from elementary school students, 130 questionnaires were applied to one fifth-grade class, one sixth-grade class, and two seventh-grade classes. A total of 122 questionnaires with open and closed questions about prior knowledge regarding indigenous peoples, their culture, and their physical practices were collected, along with the consent form signed by the guardians. The data from this research revealed the invisibility of indigenous knowledge in schools. During the same period, initial semi-structured interviews were conducted with Physical Education teachers working with these students. The results of these interviews aligned with those of the students, demonstrating the need for the production of materials that contribute to the development of knowledge about indigenous culture and their physical practices. Therefore, an educational product was chosen, constructed with the knowledge related to the research with the intercultural indigenous licensure students, who brought suggestions of physical practices for regular physical education. This material was produced in text format, developed during the Professional Master's in Teaching in Basic Education of the Stricto Sensu Postgraduate Program of CEPAE/UFG. As a result of the process, the e-book "Indigenous Physical Practices in School Physical Education" was created, evaluated at the end by the Physical Education teachers involved in the research.